Линейные системы в теории автоматического управления: учебное пособие - Шилин А. А. Александр Анатольевич; Ляпунов Д. Ю. Данил Юрьевич; Паюк Л. А. Любовь Анатольевна; Ляпушкин С. В. Сергей Викторович (Томск, Изд-во ТПУ, 2019)
Заглавие с титульного экрана